Peradilan Etik dan Etika Konstitusi [Court of Ethics and Constitutional Ethics] - Ayuni, Qurrata (UI Scholars Hub, 2016)
This book presents an idea on making a court of ethics in Indonesia, written by Indonesia’s famous scholar in Constitutional Law, Prof. Dr. Jimly Asshiddiqie. This book has brought new perspectives by advancing the existence of law of ethics in the domination of rule of law.